Penyuluhan Perilaku Hidup Bersih Dan Sehat Siswa Siswi Sekolah Dasar Negeri Nunudi Kecamatan Sarudu Kabupaten Mamuju Utara Provinsi Sulawesi Barat - Agustinus Talindong (AMMA : Jurnal Pengabdian Masyarakat, 2022)
Clean and healthy living behavior (PHBS) is a set of behaviors that are practiced on the basis of awareness as a result of learning that makes a person help himself (independently) in the health sector and play an active role in realizing public health. Based on initial observations made at the school, that there is often trash wrapped around students' snacks in the school gutter, then asking the student how many days to change the school uniform the students answered that the red and white clothes were worn for 3 days, namely Monday, Tuesday and Wednesday without changing. The purpose of this counseling is for students to have clean and healthy living behavior at the Nunu State Elementary School in Sarudu District. To find out clean and healthy living behavior. Using primary data and secondary data. Collecting data using a questionnaire with 30 assessment items with knowledge, attitudes and actions using univariate analysis. The population in this extension is all students at the State Elementary School in Nunu Village, Sarudu District. The sample was all sixth grade students with a sample of 65 respondents. The results of the counseling showed that good knowledge was (36.9%), sufficient knowledge (29.2%), less knowledge (33.8%), while attitudes good (32.3%), sufficient attitude (29.2%), lacking attitude (38.5%) and good action (49.2%), sufficient action (16.9%), less than 22(33,8)